Disagreement in normative IGF‐I levels may lead to different clinical interpretations and GH dose adjustments in GH deficiency - Varewijck, A.J.; van der Lely, A.J.; Neggers, S.J.C.M.M.; Hofland, L.J.; Janssen, J.A.M.J.L. (Clinical endocrinology (Oxford), 2018)
Summary Introduction and Background Normative data for the iSYS IGF‐I assay have been published both in the VARIETE cohort and by Bidlingmaier et al. Objective To investigate whether normative data of the VARIETE cohort lead to differences in Z‐scores for total IGF‐I and clinical interpretation compared to normative data of Bidlingmaier et al. Design We used total IGF‐I values previously measured by the IDS‐iSYS assay in 102 GH‐deficient subjects before starting GH treatment and after 12 months of GH treatment. Z‐scores were calculated for all samples by using the normative data of the VARIETE cohort and by the normative data reported by Bidlingmaier et al. Result Before GH treatment, Z‐scores calculated by using the normative data of the VARIETE cohort were significantly lower than those calculated by the normative data of Bidlingmaier et al: −2.40 (−4.52 to +1.31) (mean [range]) vs. −1.41 (−3.14 to +1.76); P < .001). After 12 months of GH treatment, again the Z‐scores based on the normative data of the VARIETE cohort were significantly lower than those based on the normative data of Bidlingmaier et al: −0.65 (−4.32 to +2.79) vs 0.21 (−3.00 to +3.28); P < .001). Conclusion IGF‐I Z‐scores in 102 GH‐deficient subjects differed significantly when normative data from two different sources were used. In daily clinical practice, this would most likely have led to different clinical interpretations and GH dose adjustments.